DESAIN SISTEM OTOMASI DAN PENGENDALIAN SUHU BERBASIS TEMPERATURE CONTROLLER PADA USAHA AIR REBUS” - Riyadi, Slamet; Syamsuri, Heris; Setiawan, Tia (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The Boiled Water Business (UAR) in Kertasari Village, Ciamis Regency is one of the micro-enterprises that focuses on providing hygienic drinking water through a boiling process. The production process, which is still done manually, leads to several problems, such as unstable water temperature, potential hazards for operators due to exposure to hot water, inefficient production time, and energy wastage. This research aims to design and create an automation and temperature control system based on a microcontroller, equipped with a cooling system, so that the water boiling process becomes more efficient, safe, and stable. This system is designed to automatically regulate the water temperature until it reaches boiling point (100°C) using a temperature sensor connected to the microcontroller, and automatically channels the water to the cooling system through a solenoid valve once the temperature is reached. The research method used is research and development with an experimental approach, which includes stages of system design, component selection, hardware assembly, microcontroller programming, and performance testing of the system in a real operational environment. The results of this research are expected to improve the efficiency of UAR production by minimizing manual intervention, reducing energy consumption, accelerating the cooling process, and lowering the risk of workplace accidents. With this system, the Boiled Water Enterprise can operate more optimally and consistently in meeting the hygienic standards of drinking water.